Moderating Role of Perceived Benefit on the Relationship between Attitude and Actual Purchase - Sarina Ismail; Sany Sanuri Mohd Mokhtar (International Review of Management and Marketing, 2016)
Herbs have been used around the world since thousands of years ago, now, 80% of world population are using herbs as part of  health practices and treatment of diseases. Due to the increasing interest on herbal products, the global herbal industry have expanded tremendously due to lifestyle changes caused by modernization and health problems. With the increase demand and usage of the herbal product, studies related to actual purchase is considered as limited. Hence,the main objective of the study is to investigate factors that influence the actual purchase related to herbal products. This study has enhanced the understanding factors that influence  actual purchase and will provide insightful information to the entrepreneurs regarding the actual purchase of herbal products. Therefore, SMARTPLS was used in testing the interrelation between the proposed research model, the result shows that, perceived benefit  moderates the relationship between attitude and actual purchase. In the last section,  theoretical and practical implications of the study are discussed.